2017
DOI: 10.3390/ijfs5010004
|View full text |Cite
|
Sign up to set email alerts
|

Policy Impact on the Chinese Stock Market: From the 1994 Bailout Policies to the 2015 Shanghai-Hong Kong Stock Connect

Abstract: Abstract:From the 1994 bailout policies to the 2015 Shanghai-Hong Kong Stock Connect, the policy impact on the Chinese stock market has changed over time. By May 2015, global investors can directly invest in a more legalized and normalized Chinese stock market, whereas they are still concerned about the policy-oriented market and its attendant risks. In this study, we employ the family of GARCH models to investigate the structural changes in risks with the implementation of a series of policies. Our results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 30 publications
2
23
0
2
Order By: Relevance
“…Besides, SH-HK and SZ-HK Stock Connect turnovers gradually increase throughout the year. We find that there is a continuous uptrend of Stock Connect turnover and an increasing cointegration of Mainland China and Hong Kong stock market, consistent with Wang and Chong (2018), Wang et al (2017) and Huo and Ahmed (2017). 9.056 × 10 9 1.945 × 10 9 5.897 × 10 9 5.423 × 10 9 5.321 × 10 9 3.284 × 10 9 Median 1.984 × 10 10 8.705 × 10 9 1.782 × 10 9 4.855 × 10 9 4.864 × 10 9 4.844 × 10 9 3.001 × 10 9 Maximum 8.571 × 10 10 1.573 × 10 10 5.702 × 10 9 2.352 × 10 10 2.536 × 10 10 1.273 × 10 10 1.327 × 10 10 Minimum 7.057 × 10 9 4.514 × 10 9 5.260 × 10 8 6.887 × 10 8 3.965 × 10 8 6.746 × 10 8 3.502 × 10 8 SD 1.463 × 10 10 2.139 × 10 9 6.800 × 10 8 3.523 × 10 9 3.661 × 10 9 2.758 × 10 9 2.164 × 10 9 Skewness 1.654 0.392 Table 5a,b shows the correlation matrices ofmarket RVs, market volumes, and all Stock Connect turnovers.…”
Section: Data Summarysupporting
confidence: 79%
See 1 more Smart Citation
“…Besides, SH-HK and SZ-HK Stock Connect turnovers gradually increase throughout the year. We find that there is a continuous uptrend of Stock Connect turnover and an increasing cointegration of Mainland China and Hong Kong stock market, consistent with Wang and Chong (2018), Wang et al (2017) and Huo and Ahmed (2017). 9.056 × 10 9 1.945 × 10 9 5.897 × 10 9 5.423 × 10 9 5.321 × 10 9 3.284 × 10 9 Median 1.984 × 10 10 8.705 × 10 9 1.782 × 10 9 4.855 × 10 9 4.864 × 10 9 4.844 × 10 9 3.001 × 10 9 Maximum 8.571 × 10 10 1.573 × 10 10 5.702 × 10 9 2.352 × 10 10 2.536 × 10 10 1.273 × 10 10 1.327 × 10 10 Minimum 7.057 × 10 9 4.514 × 10 9 5.260 × 10 8 6.887 × 10 8 3.965 × 10 8 6.746 × 10 8 3.502 × 10 8 SD 1.463 × 10 10 2.139 × 10 9 6.800 × 10 8 3.523 × 10 9 3.661 × 10 9 2.758 × 10 9 2.164 × 10 9 Skewness 1.654 0.392 Table 5a,b shows the correlation matrices ofmarket RVs, market volumes, and all Stock Connect turnovers.…”
Section: Data Summarysupporting
confidence: 79%
“…Burdekin and Siklos (2018) documents that the A-H premium between Hong Kong and Mainland China's stocks rose substantially from slightly under 100% when the program was launched to nearly 150% in early 2016. In addition to the A-H premium studies, Wang et al (2017) find significant effects of the Stock Connect on both Shanghai and Shenzhen stock market volatility using daily data, although the impact on the Hong Kong market is minimal. Huo and Ahmed (2017) investigate the impact of the SH-HK Stock Connect and conclude that Stock Connect significantly strengthened volatility spillover between the two markets.…”
Section: Introductionmentioning
confidence: 96%
“…Therefore, although unsolved, the puzzles of China's stock market seem to make sense considering its features, such as over‐speculation by investors, domination by SOEs, and excessive intervention of the Government. What is more, China's stock market has been developing rapidly and thus its mechanism may change as time passes (Tsai et al ., ; Wang et al ., ). Though China is currently undergoing an economic transition, few studies offer a comprehensive understanding of what is happening in China's stock market.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Additionally, stock market helps to attract more savings into productive investment and prevent the early withdrawal of capital invested in the long-term projects. King and Levine (1993), Rasmiah and Rasmiah (2016) and Wang, Tsai and Li (2017) also suggested another approach to identify the channel of transmission between financial markets and economic growth-financial markets help the functioning of efficient resource allocation. Therefore, an economy with a well-functioning financial market will have a higher productivity growth rate.…”
Section: Endogenous Growth Theorymentioning
confidence: 99%
“…Most of these stock markets still suffer the problems of low liquidity, higher cost of trading, unstable exchange and inflation rates, declined in growth domestic product, low frequency trading, information and disclosure deficiencies, poor supervision and regulatory framework and political instability (Okoye, Modebe, Taiwo & Okorie, 2016;Popoola et al, 2017;African Capital Market News, 2018). Furthermore, studies have shown that countries with low level of corruption practices and well-functioning, sound and developed stock market experienced drop in poverty levels, increased in foreign investment inflow and well-functioning economic activities grow more rapidly than those countries with high level of corruption and weak economic indices (Andrianaivo & Yartey, 2009;Beck, Maimbo, Faye & Triki, 2011;Oshaibat, 2016;Wang, Tsai & Li, 2017).…”
Section: Introductionmentioning
confidence: 99%